2021
DOI: 10.32859/era.22.16.1-16
|View full text |Cite
|
Sign up to set email alerts
|

Edible and Medicinal Pteridophytes of Nepal: A Review

Abstract: Background: Traditional use of pteridophytes as food and medicine is a common practice around the world. Many ethnic communities hold vast knowledge about the uses of pteridophytes and the documentation of such knowledge and biodiversity of edible and medicinal pteridophytes is important for health care, food security and conservation. Although being one of the biodiversity rich countries, the detailed use of edible and medicinal pteridophytes from Nepal is not well documented and they are one of the underutil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…We could not find proper documentation for these pteridophytes as wild edible ferns of Nepal; therefore, they are omitted in the list. The pteridophytes, which consumed for the medicinal values, but not eaten as salad or cooked vegetables, are also not included in the table [ 71 ].…”
Section: A List Of Wild Edible Ferns Of Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not find proper documentation for these pteridophytes as wild edible ferns of Nepal; therefore, they are omitted in the list. The pteridophytes, which consumed for the medicinal values, but not eaten as salad or cooked vegetables, are also not included in the table [ 71 ].…”
Section: A List Of Wild Edible Ferns Of Nepalmentioning
confidence: 99%
“…It has been recently reported that there are 582 taxa of pteridophytes in Nepal [ 72 ]; however, Nepalese researchers have not been focused in the ethnopteridological studies in traditional medicinal knowledge, food safety and phytoconstituents present in the pteridophytes. At the same time, surprisingly, very few scientific studies have been carried out globally in the areas of the chemical constituents and pharmacological activites of pteridophytes [ 71 ]. In this section, we accumulate available information on the distribution, ethnomedicinal uses, pharmacognosy and phytochemistry of the wild edible ferns listed in Table 1 .…”
Section: Distribution Ethnomedicine Pharmacognosy and Phytochemistry ...mentioning
confidence: 99%
“…A total of 24 species of edible ferns are reported to be consumed in Nepal in the form of vegetable and pickles (Ojha & Devkota 2021). Pteridaceae is the family with the highest number of edible and medicinal species in Nepal (Ojha, & Devkota 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 24 species of edible ferns are reported to be consumed in Nepal in the form of vegetable and pickles (Ojha & Devkota 2021). Pteridaceae is the family with the highest number of edible and medicinal species in Nepal (Ojha, & Devkota 2021). Diplazium esculentum is one of the most common vegetables of fern and other species such as Diplazium maximum, Ophioglossum petiolatum, Dryopteris cochleata, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Asia-Tropical has approximately three times more reviewed literature uses of ferns than South America (7). Ferns are currently considered a source of polar phytochemicals as phenolic acids and flavonoids with therapeutic and nutritional value in eastern countries, especially in Nepal, India, and China (8)(9)(10). This is the case of some ferns described in the traditional Chinese medicine, as the case of Pteridium aquilinum (L.) Kuhn (Dennstaedtiaceae) (10).…”
Section: Introductionmentioning
confidence: 99%